4K-memristor analog-grade passive crossbar circuit - H. Kim (Nature Portfolio, 2021)
The superior density of passive analog memristive devices can potentially enable efficient implementation of very large scale neural networks; however, device to device variability is currently too large to take advantage of this. Here, Kim et al demonstrate an impressive reduction in this variability, with a large passive memristive array.